Fundamentals of database management systems - Gillenson, Mark L. (Hoboken, NJ : Wiley, 2023)
'The New Corporate Resource The development of database management systems, as well as the development of modern computers, came about as a result of society's recognition of the crucial importance of storing, managing, and retrieving its rapidly expanding volumes of business data. To understand how far we have come in this regard, it is important to know where we began and how the concept of managing data has developed. This chapter begins with the historical background of the storage and uses of data and then continues with a discussion of the importance of data to the modern corporation.'--
Includes index.
Keywords: Database management